2011
DOI: 10.5468/kjog.2011.54.12.836
|View full text |Cite
|
Sign up to set email alerts
|

A giant endometrial polyp with tamoxifen therapy in postmenopausal woman

Abstract: Tamoxifen is a synthetic non-steroid anti-estrogen that has been used effectively for several years in the adjuvant treatment of breast cancer. But, the drug has been associated with development of endometrial poylp, hyperplasia and adenocarcinoma possibly mediated through its agonistic estrogen properties during the menopausal period in which estrogens are at a low level. Endometrial polyp has been described as the most common endometrial pathology in association with postmenopausal tamoxifen treatment. We pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…Giant endometrial polyps, as seen in the present case study, are exceedingly rare variants of classical polyps. According to the pertinent world literature, there are <15 cases of giant endometrial polyps which have been reported so far[56891011121920212223] and a very small number have been documented from India. [2021] On reviewing the handful of cases mentioned till date, various clinicopathological features of this rare entity draws the attention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Giant endometrial polyps, as seen in the present case study, are exceedingly rare variants of classical polyps. According to the pertinent world literature, there are <15 cases of giant endometrial polyps which have been reported so far[56891011121920212223] and a very small number have been documented from India. [2021] On reviewing the handful of cases mentioned till date, various clinicopathological features of this rare entity draws the attention.…”
Section: Discussionmentioning
confidence: 99%
“…Most of them are usually <2 cm in diameter, however, polyps can occasionally attain a size of >4 cm and then they are designated as giant polyps. [7] Most of the giant endometrial polyps reported in the literature are mainly associated with postmenopausal tamoxifen or raloxifene treatment,[89101112] reflecting that they are affected by the hormone levels and grow in response to the circulating estrogen. These rare giant endometrial polyps are clinically important as they may cause concern to both the patient and the dealing clinician for the suspicion of a malignancy, especially because of their size and associated clinical symptoms leading to unnecessary diagnostic and therapeutic interventions.…”
Section: Introductionmentioning
confidence: 99%
“…Management of small asymptomatic polyps may be conservative with follow-up. However, conservative management should be undertaken with caution in postmenopausal patients, patients with any risk factors, or those with polyps measuring greater than 1.0–1.5 cm in size, as there is increased risk for atypical hyperplasia or malignancy [ 7 , 15 ]. Risk factors for malignancy differ among reports and populations; however, larger size, advanced age, menopausal status, obesity, diabetes, arterial hypertension, and tamoxifen use have been associated with malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…5 In this report, we describe the case of a giant 8x4x3 cm endometrial polyp originating from the posterior wall of the uterine cavity that extended to the external cervical os and protruded into the vagina. The clinical, radiological, hysteroscopic and histopathologic data of this entity have been discussed according to the literature.…”
Section: Giant Endometrial Polypmentioning
confidence: 99%
“…2,3 Giant polyps usually occur secondary to high estrogen levels or tamoxifen therapy after breast cancer. 4,5 Rising polyps usually originate from the endocervix and are called endocervical polyps. 2 Although giant endometrial polyps, which fill the endometrial cavity, or protruding endocervical polyps with a size greater than 4 cm are published in several cases, endometrial giant polyp Proceedings in Obstetrics and Gynecology, 2013;3(3):2…”
Section: Introductionmentioning
confidence: 99%